PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH PT BPR HOKI DI KABUPATEN TABANAN - Dewi, Ratih Kusuma; Kerti Yasa, Ni Nyoman; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.03.NO.05 TAHUN 2014, 2014)
The development of BPR especially in Bali province really promising. Industry of BPR takes a very important role in economic sector, especially in supporting micro and medium business development. The tighter competition among those BPR, themselves the service should be done more optimally, so that the company is able to win the competition. The purpose of this study was to determine the effect of service’s quality toward customer satisfaction and loyalty at PT BPR Hoki at Tabanan regency. The number of respondent on this research is defined 150 respondents. Respondents were selected by purposive sampling method. The data processed and analyze by Structural Equation Modeling (SEM) and AMOS software. Statistical analysis showed that service quality, customer satisfaction, and loyalty has a positive and significant relationship.